A Randomized Phase II Trial of mFOLFOX6 + Bevacizumab Alone or with AdCEA Vaccine + Avelumab Immunotherapy for Untreated Metastatic Colorectal Cancer. (4th February 2022) - Redman, Jason M; Tsai, Yo-Ting; Weinberg, Benjamin A; Donahue, Renee N; Gandhy, Shruti; Gatti-Mays, Margaret E; Abdul Sater, Houssein; Bilusic, Marijo; Cordes, Lisa M; Steinberg, Seth M; Marte, Jennifer L; Jochems, Caroline; et al.
Abstract: Background: FOLFOX plus bevacizumab is a standard of care (SOC) for first-line treatment of microsatellite-stable metastatic colorectal cancer (MSS mCRC). This study randomized patients to SOC or SOC plus avelumab (anti-PD-L1) plus CEA-targeted vaccine. Methods: Patients with untreated MSS mCRC enrolled to a lead-in arm assessing safety of SOC + immuno-oncology agents (IO). Next, patients were randomized to SOC or SOC + IO. The primary endpoint was progression-free survival (PFS). Multiple immune parameters were analyzed. Results: Six patients enrolled to safety lead-in, 10 randomized to SOC, and 10 to SOC + IO. There was no difference in median PFS comparing SOC versus SOC + IO (8.8 months (95% CI: 3.3-17.0 months) versus 10.1 months (95% CI: 3.6-16.1 months), respectively; hazard ratio 1.061 [ P = .91; 95% CI: 0.380-2.966]). The objective response rate was 50% in both arms. Of patients analyzed, most (8/11) who received SOC + IO developed multifunctional CD4+/CD8+ T-cell responses to cascade antigens MUC1 and/or brachyury, compared to 1/8 who received SOC alone ( P = .020). We detected post-treatment changes in immune parameters that were distinct to the SOC and SOC + IO treatment arms. Accrual closed after an unplanned analysis predicted a low likelihood of meeting the primary endpoint. Conclusions: SOC + IO generated multifunctional MUC1- and brachyury-specific CD4+/CD8+ T cells despite concurrent chemotherapy. Although a tumor-directed immune response is necessary for T-cell–mediated antitumor activity, it was not sufficient to improve PFS. Adding agents that increase the number and function of effector cells may be required for clinical benefit. Abstract : This article presents the findings of a randomized phase II clinical trial comparing FOLFOX-based standard of care to FOLFOX-based standard of care plus avelumab plus AdCEA vaccine. Prospective studies of effects of FOLFOX plus bevacizumab on circulating cascade antigen-specific T cells, peripheral blood immune cell subset frequencies, serum cytokines, and soluble factors are also reported.